P628 Tofacitinib in pediatric ulcerative colitis: a retrospective multi-center experience from the Paediatric IBD Porto group of ESPGHAN. (30th January 2023) - Ledder, O; Dubinsky, M; Dolinger, M; Fatima, A; Suskind, D; Scarlett, J; Röeser, D; Shouval, D; Meyer, G; Molle Rios, Z; Pujol, G; Lozano, A; et al.
Abstract: Background: Tofacitinib, a Janus kinase (JAK) inhibitor, has recently been approved for treatment of moderate to severe active ulcerative colitis (UC) in adults. Data on efficacy and safety in pediatrics are limited. In this multicenter study from the Paediatric IBD Porto group of ESPGHAN, we describe the short-term effectiveness and safety of tofacitinib in an international pediatric IBD cohort. Methods: Retrospective review of children (2-18 years) diagnosed with UC treated with tofacitinib from 15 pediatric centers internationally. Primary outcome was corticosteroid-free clinical remission (PUCAI<10) at week 8, with secondary outcomes including clinical response (≥20 point decrease in PUCAI), colectomy rate and safety. Primary outcome was calculated utilizing non-response imputation (NRI), whereby drug cessation for any reason was considered treatment failure. Results: 78 patients (43 (55%) female, mean age at diagnosis 12.5 (±2.7) years, median disease duration 20 months (IQR 10.3-38.8)), all with previous biologic failure, including 20/78 (26%) with previous failure of three biologic classes. 15/78 (19%) patients achieved corticosteroid-free clinical remission at week 8 with a further 18/78 (23%) demonstrating clinical response. 9/78 (12%) underwent colectomy by week 8, and 21/78 (27%) by week 24. Twelve adverse events were reported including five infective (three of which deemed possibly related to treatment – zoster, HSV-2 cheilitis and septic arthritis), one case of pancreatitis, and abnormal blood test results in 5 children (anemia, lymphopenia, elevated hepatic transaminases and hypercholesterolemia). Conclusion: In this largest real-life cohort of tofacitinib in pediatric UC to date, tofacitinib seemed effective in at least 19% of highly refractory patients by week 8. Adverse reactions and safety were largely consistent with adult data.